2002
DOI: 10.1007/s004150200064
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment after viral meningitis in adults

Abstract: Viral meningitis in adults results in mild cognitive impairment in a significant proportion of patients that is not identified by clinical examination or cognitive screening tests. Nevertheless, even mild deficits in non-verbal learning and cognitive speed might lead to overstrain and handicap in complex situations of daily living and working. We therefore recommend that the neuropsychiatric evaluation of all patients with intracranial infections include neuropsychological testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In the acute clinical phase, it may be difficult to distinguish between meningitis and encephalitis. Non-specific and overlapping neurological findings have been reported (2,5), and the term meningoencephalitis has been accepted. Magnetic Resonance Imaging (MRI) visualizes parenchymal damage in the acute stage, but no studies have used MRI to predict neuropsychiatric sequelae after aseptic meningitis (2,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the acute clinical phase, it may be difficult to distinguish between meningitis and encephalitis. Non-specific and overlapping neurological findings have been reported (2,5), and the term meningoencephalitis has been accepted. Magnetic Resonance Imaging (MRI) visualizes parenchymal damage in the acute stage, but no studies have used MRI to predict neuropsychiatric sequelae after aseptic meningitis (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest long-term postinfectious neuropsychiatric symptoms, although the prevalence and nature remain unclear (1). Even subtle neuropsychiatric symptoms may have a substantial negative impact on the quality of life, social wellbeing, and work performance (2).…”
mentioning
confidence: 99%
“…Secondly, from the adult patient's point of view, the wide range of available biological tools allow physicians to discharge them with a precise etiologic diagnosis rather than a presumed diagnosis of viral meningitis. Finally, a recent study suggested that viral meningitis may not be a so-called benign outcome disease, in that a significant proportion of patients exhibited long-term mild cognitive impairment [Sittinger et al, 2002]. Improvement in pathophysiological understanding of these cognitive disorders may benefit from accurate etiologic diagnosis in aseptic meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one patients (25 ± 12 months after viral meningitis) performed significantly worse on tasks testing non-verbal memory, attention and speed of cognitive performance than 21 healthy control persons, and 40 % of patients were classified as suffering from cognitive impairment [23]. Schmidt and co-workers studied 59 patients 1 to 12 years after viral meningitis without concomitant encephalitis.…”
Section: Viral Meningitismentioning
confidence: 99%